Extent of Use and Effectiveness of Learner-Centered and Teacher-Centered Approaches Among Senior High School Teachers in Jolo - Ladjahasan, Al-Micha-el D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This research explored the utilization and effectiveness of teacher-centered (TC) and student-centered (LC) methods in public and private senior high schools LIA Jolo. More particularly, its aims were as follows: (1) to ascertain the extent of usage of TC and LC methods; (2) to explore variations in the usages according to school type; (3) to assess their efficiency; (4) to make comparisons of efficiency by category according both categories of schools and types of teachers profile. All Senior High Schools, both public and private with a census of 139 teachers participated. Surveys were used to collect information about the use of and perception of effectiveness of both approaches. Descriptive and inferential statistics were used to analyse the significant differences on under school type, teachers’ demographic profile. Results show that both LC and TC are widely implemented in public and private schools, however they significantly differ. LC is more common in private schools and TC prevails in public schools. The results also showed that LC is highly preferred compared to TC in terms of perceived effectiveness by the respondents. LC was rated more effective by private school teachers (93) when compared with public schools teachers (46). In contrast, TC did not differ significantly in its effectiveness among public versus private schools. Furthermore, teachers' gender and age were not relevant where the perceived usefulness of both approaches was concerned.